Osteogenesis Imperfecta in A Neonate with A Positive Family History: A Case Report - Bryantdary Arrafif Nasution; Shinta Nareswari (Medula, 2026)
Osteogenesis Imperfecta (OI) is a rare genetic disorder characterized by bone fragility due to impaired type 1 collagen synthesis. This condition is generally caused by mutations in the COL1A1 and COL1A2 genes, which are inherited in an autosomal dominant or recessive manner, and are clinically heterogeneous. This report presents a case of a 5-day-old male neonate, born by cesarean section at 37 weeks of gestation, with a birth weight of 2,200 grams, who was referred to Dr. H. Abdul Moeloek Regional General Hospital, Bandar Lampung, with complaints of inactive right leg movement since 4 days of age. There was a positive family history, namely an older sibling who had been diagnosed with OI. Physical examination revealed bilateral blue sclerae, asymmetry in the lengths of the lower extremities, and pain with mobilization of the right leg. Radiological examination in the form of a right femur x-ray and bone survey showed a complete proximal fracture of the right femur, bowing of the left femur, and decreased bone density, which supports the diagnosis of OI. Serum Alkaline Phospatase (ALP) levels were within normal limits, distinguishing them from rickets or hypophosphatasia. Management included splinting immobilization, closed reduction, hip spica placement, prophylactic antibiotics and analgesics, and phototherapy for hyperbilirubinemia. The prognosis for this patient was quo ad vitam (dubia ad bonam), while quo ad functionam and quo ad sanationam (dubia ad malam) were quo ad functionam. This case report aims to raise clinical awareness of OI in the neonatal period, especially in cases with a confirmed family history.